Revisiting The Exchange Rate Pass-Through in Turkey Economy: Evidence from Structural VAR Model - ÖZER, Hüseyin; KUTLU, Muhammet (International Journal of Contemporary Economics and Administrative Sciences, 2022)
The purpose of this article is to examine the pass-through of exchange rate fluctuations on the domestic price level in Turkey. To this effect, the interaction between exchange rate fluctuations, producer price index, and the consumer price index was analyzed using the SVAR model. The degree of exchange rate pass-through was examined with the help of cumulative ERPT elasticities based on impulse response functions. Besides, the monetary policy interest rate variable is also included in the model to make inferences about the CBRT’s policy stance against the exchange rate and price fluctuations. Study findings reveal that exchange rate pass-through is incomplete in Turkey, however, there is a high degree of pass-through of exchange rate fluctuations to producer prices than there is to consumer prices. Study results also point that the CBRT’s policy interest rate is not an important determinant of the exchange rate and price levels. However, Central bank policies with stable and reliable commitments are recommended.